School Strategies in Developing Students’ Character in Elementary Schools - M. Fadhil; Zulkhairi Zulkhairi (CV. Lentera Literasi Indonesia, 2026)
This study examines school strategies in shaping students’ religious, disciplinary, and environmental care character in elementary education. Employing a qualitative descriptive research approach, data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and fifth-grade students at SD Negeri 012 Candirejo. The findings indicate that character education strategies are implemented through systematic planning, integration of character values into learning activities, consistent enforcement of school regulations, and daily habituation practices. Key activities such as religious routines, discipline enforcement, environmental care programs, and teacher role modeling significantly contribute to the internalization of character values among students. Supporting factors include strong school leadership, teacher consistency, and a supportive school culture, while inhibiting factors involve variations in students’ behavioral readiness and limited external support. This study concludes that structured, school-based character education strategies are effective in fostering students’ character development at the elementary level.